Literasi media sosial di kalangan mahasiswa ilmu perpustakaan Universitas Lancang Kuning - Maya Oktaviani; Rosman H; Hadira Latiar (FPPTI Jawa Tengah, 2022)
The title of this research is Analysis of Media Literacy Students of the Lancang Kunning University Library Department. The purpose of this study was to determine the level of social media literacy of students in the Library Department of Lancang Kunning University. The method used in this research is descriptive quantification method. Data collection techniques used in this study were observation, questionnaires, documentation, interviews, and literature study. The population and sample of this study used a saturated sample, namely the number of active Lancang Kuning University Library Science students in 2022 as many as 197 people. This study uses data analysis techniques using the mean (calculated mean) and grand mean formulas. The results of the study found that the level of social media literacy was at a good level, namely 3.61, with a range of 3.20 to 4.20. The author suggests to students of the Library Department of Lancang Kunning University to continue to improve their social media skills and be better able to use social media as a forum for disseminating information. This can be achieved through literacy activities especially on social media, and increasing awareness of the importance of social media literacy when using social media. Social media competence can also be developed through daily activities in virtual communication by using social media as a virtual communication platform.